(untitled) (قضايا سياسية, 2024)
Since the outbreak of the war between Russia and Ukraine in February2022 , one of which has been dramatically accelerating, Their effects are reflected in all aspects, including the International economy, International markets soon began to show signs of imbalance and turmoil. by governing Russia's and Ukraine's economic standing at the international level, and by the process of interconnectedness and Mutual dependence in the international economy in accordance with the theory of Mutual dependence, A quick look at the transformations that have characterized the world economy since the Second World War, we see that the world economy has become a vast arena of variables that vary in intensity from point to point. and those variables include a continuous set of dimensions, which in turn demonstrate the strength and effectiveness of those transformations in the international economy, That economy has become a single mass and any impact on any part of that mass is affected by all the other blocks in different proportions and thus, the Russian-Ukrainian war's outcomes were imbalances in most International markets and high inflation rates for International prices of goods and services, as well as the worsening International food crisis, rising energy prices and declining International financial markets.